Three Cases of Previous Smokers with Rheumatoid Arthritis Who Did Not Respond to Tumor Necrosis Factor Inhibitors Were Treated Successfully with an Anti-Interleukin-6 Receptor Antibody - Yasuo Iwata (Case Reports in Rheumatology)
We report three cases of previous smokers who did not respond to TNF inhibitors but who responded successfully to an anti-interleukin-6 receptor antibody (tocilizumab (TCZ)). Case 1 is a 63-year-old woman whose smoking index was 200 and had been complaining of polyarthralgia since 1996. She started treatment with etanercept due to high disease activity, but her DAS28-CRP was 4.2. She was therefore switched to TCZ, which dramatically improved her symptoms; her DAS28-CRP had decreased to 2.1. Case 2 is a 64-year-old man whose smoking index was 1600 and had been complaining of polyarthralgia since 2006. Because his DAS28-CRP score increased over time to 5.9, etanercept and adalimumab were added sequentially, but he showed no response over the course of two years. The patient was therefore switched to TCZ, which dramatically improved his symptoms: his DAS28-CRP decreased to 2.7. Case 3 is a 48-year-old woman whose smoking index was 560 and had been complaining of pain in both knee joints since 2001. She was treated with adalimumab due to high disease activity but showed no response over the course of 1.5 years. The patient was therefore switched to TCZ, and her DAS28-CRP decreased to 1.8. An IL-6 blockade might be suitable for treating these 3 cases of previous smokers.